2019
DOI: 10.1002/cjoc.201900071
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Growth of Halide Perovskite Single Crystals: From Methods to Optimization Control

Abstract: Metal halide perovskites are emerging as new generation optoelectronic materials due to their high carrier mobility, long carrier diffusion length and large light absorption coefficient, which have broad applications in solar cell, light-emitting diode, laser, photodetector and transistors. Perovskite single crystal is an ideal platform for discerning the intrinsic properties of these materials. In some cases, perovskite single crystals are better candidates to gain high performance optoelectronics. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 123 publications
0
15
0
Order By: Relevance
“…Solvent evaporation crystallization method based on precipitation of the precursor(s) from solution upon evaporation of solvent, is a common strategy used to fabricate crystalline materials 49,50. Despite the widespread use of this protocol to synthesize lead halide perovskites including both organic–inorganic (i.e., CH 3 NH 3 PbX 3 )51 and all‐inorganic (i.e., CsPbX 3 ) (X = Cl, Br, I)52,53 compounds, to the best of our knowledge, copper based lead‐free perovskites have not yet been fabricated by this technique. Herein, all‐inorganic 0D Cs 3 Cu 2 I 5 crystals were prepared at room temperature by the solvent evaporation crystallization process, using CsI and CuI as precursor materials and DMF as a solvent, as shown in Figure a.…”
Section: Figurementioning
confidence: 99%
“…Solvent evaporation crystallization method based on precipitation of the precursor(s) from solution upon evaporation of solvent, is a common strategy used to fabricate crystalline materials 49,50. Despite the widespread use of this protocol to synthesize lead halide perovskites including both organic–inorganic (i.e., CH 3 NH 3 PbX 3 )51 and all‐inorganic (i.e., CsPbX 3 ) (X = Cl, Br, I)52,53 compounds, to the best of our knowledge, copper based lead‐free perovskites have not yet been fabricated by this technique. Herein, all‐inorganic 0D Cs 3 Cu 2 I 5 crystals were prepared at room temperature by the solvent evaporation crystallization process, using CsI and CuI as precursor materials and DMF as a solvent, as shown in Figure a.…”
Section: Figurementioning
confidence: 99%
“…In recent years, with the increasing demand for radiation detection materials in many aspects, researchers have conducted extensive researches on scintillators. Perovskite materials have been proved to be a potential scintillator material due to their excellent properties, [ 163,164 ] but their applications are scarce. Therefore, in this chapter, we mainly summarize the current research challenges and the feasibility analysis for scintillators, and provide a simple outlook for the future development.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…[ 1 ] Due to their unique optoelectronic properties such as long charge carrier lifetime, [ 2 ] high absorption coefficient, [ 3 ] high charge carrier mobility, [ 4‐5 ] and flexible band structure engineering, [ 6‐7 ] along with their low processing cost, [ 8 ] the halide perovskite materials are promising candidates for highly efficient and cost‐competitive solar conversion devices. [ 9 ] More recently, it has been reported that the halide perovskite materials show unique activities in the photocatalytic conversion of multiple chemicals. [ 10 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%